Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Use the inequality to answer the following question. 2 ( x − 7 ) ≤ 6 x + 15 Which of the following inequalities could be the result of the first step in solving the inequality for x?

Sagot :

2 (x - 7)

Because PEMDAS solve the parentheses first
x≥-29/4

Step by step explanation:

2x−2·7≤6x+15

2x−14≤6x+15

(2x−14)+(14−6x)≤(6x+15)+(14−6x)

(2x−14)+(−6x+14)≤(6x+15)+(−6x+14)

2x−14−6x+14≤6x+15−6x+14

2x−6x−14+14≤6x−6x+15+14

−4x≤29

x≥−29/4


Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.